Kajian Ketepatan Indikasi Penggunaan Alprazolam pada Pasien Stroke di Bangsal Rawat Inap Neurologi Rumah Sakit Stroke Nasional Bukittinggi - Rika Sepriani; Fatma Sri Wahyuni; Almahdy Almahdy; Khairil Armal (Fakultas Farmasi Universitas Andalas, 2014)
Cerebrovascular disease such as stroke remains one of diseases that causes disability and death in the world. Having sufficient quality and quantity of good sleep is one important part of the healing process. Sleep disorders also increase the patient’s risk of developing recurrent stroke. The objective of this study was to analyze the accuracy of the indications for alprazolam in patients with stroke in neurology ward of National Stroke Hospital Bukittinggi, Indonesia. The study was conducted on November 2011 to February 2012 with the prospective method through observations on the condition of the patients, medical records, drug instruction cards, and the nursing care records of stroke patients who use alprazolam. Data were analyzed descriptively based on the treatment standards related to inaccuracy: alprazolam use without medical indications and indications which were not treated. The study showed that of 35 patients taking alprazolam, 1 of them was without medical indication 1 (3.45%) and another 1 was categorized as untreated indication (3.45%) of 29 incidences of drug related problems (DRP).